Zusammenhänge zwischen Klima und Vegetation am Ostabfall der mexikanischen Meseta - Lauer, Wilhelm (ERDKUNDE, 1973)
The eastern mountain slopes of Central Mexico-lying on the edge of the tropics-shows in its climatological and geobotanical structure numerous interference phenomena with tropical and extra-tropical characteristics. The plant cover has the properties of a floristic mixture of boreal, neotropical and tropical mountain/southern hemisphere elements. The thermal and hygral occurrences during the year also clearly show a transitional and boundary situation, even though the median climatic behaviour still fulfils the criteria of a tropical definition. This state of affairs is investigated in individual thermal and hygral characteristics of the climate and the convergences to the vegetation demonstrated. Particular climatic characteristics investigated include: cold air influxes in winter, the temperature gradient with increasing altitude, frost frequency and the levels of maximum precipitation.